Spectral-Based Estimation of the Local Azimuth Ambiguity-to-Signal Ratio in SAR Images - Villano, Michelangelo; Krieger, Gerhard (IEEE Transactions on Geoscience and Remote Sensing, 2014)
An innovative technique to estimate the local azimuth ambiguity-to-signal-ratio (AASR) in synthetic aperture radar (SAR) images is presented. Unlike the backscatter-based technique, the proposed one, based on the spectral properties of the image, does not require that the areas responsible for the ambiguity are within the focused image. Analysis of real TerraSAR-X data shows that the estimates of the proposed technique are consistent with the backscatter-based ones. Moreover, according to simulations, the proposed technique seems to provide more accurate estimates than the backscatter-based one, especially for high values of the local AASR.
DLR Import::2019-04-02
Keywords: Azimuth ambiguities; estimation; microwave remote sensing; spectral domain analysis; synthetic aperture radar